AN OVERVIEW ON MOUTH DISSOLVING FILM - Meghana, Raykar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Context: Mouth dissolving film (MDF) is an innovative approach for systemic delivery of therapeutically/ medicinally active drug substance(s). Objective: The main objectives of Oral mouth dissolving films is to provide better bioavailability of drug, to have improved permeability, quick onset of action as well as improve patient compliance Method: Preparation of films is similar to that of transdermal patch. Film when placed in mouth it get dissolve rapidly due to salivary fluid then it releases medicament(s), It will get absorbed within blood to show therapeutic action. Results: This overview provides information about formulation, technologies used in making mouth dissolving film formulations and evaluation tests carried out for the same. Conclusion: Mouth dissolving film formulations are innovative dosage form to improve the drug delivery, onset of action as well as improve patient compliance